Chapter Hidden music scenes: governmentality and contestation in postcolonial Hong Kong - Caro, Diego (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Floor 26 of Ho King Commercial Centre in Yau Ma Tei, the elevator stops. At the end of the corridor, the sound of a heavy metal band, detuned screams buffered by the cracked plywood door of a tiny music studio. Outdated factory buildings in Kwun Tong, industrial architecture gradually surrounded by new commercial and residential complexes; their precarious wait for urban renewal has offered an opportunity for young musicians to establish music studios, classrooms, or improvised bedrooms where music and teenage discoveries mingle with the noise of machinery. A rusty anonymous intercom partially hidden by some plastic ivies. Past the door, a narrow metallic staircase, source of random encounters and only access point to a one-off experience; hundreds of people-local and foreigners-gathered in a tiny dark room, a miscellany of sweat, smoke, voices, and distant music. The hidden networks formed by musicians scattered in unexpected venues around Hong Kong provide a sonic collage that reformulates some of the city's social peripheries from within. Through emergent sub-cultures, young artists deploy a wide range of tactics to counter the commodification and politicization of creativity, and the speculation over space in order to achieve new opportunities in a "bureaucratic society of controlled consumption." In his work on everyday life, which focuses on the resistance of (extra)ordinary people to structures of power, Michel de Certeau makes reference to the idea of "silent discoverers of their own paths in the jungle of functionalist rationality." The main actors of this essay, despite feeding on and actively participating in Hong Kong's consumerism dynamics by taking references from social media, e-commerce, or shopping malls, produce "wandering lines"-or wandering sounds-with their own (syn)tactics through their artistic practices. Notably, in Hong Kong's reductionist bureaucratic system, with a strong predominance of statistics and evaluation focused on "classifying, calculating and putting into tables," these artistic rituals and reinterpretations of the city's culture often remain overlooked or hidden to the system.